Ex Situ conservation priorities for the wild relatives of Potato (Solanum L. Section Petota) - Castañeda Álvarez, Nora P.; Haan, Stef de; Juarez, H.; Khoury, Colin K.; Achicanoy Estrella, Harold Armando; Sosa, Chrystian C.; Bernau, V.; Salas, A.; Heider, B.; Simon, R.; Maxted, Nigel; Spooner, D.M. (Public Library of Science, 2015)
Crop wild relatives have a long history of use in potato breeding, particularly for pest and disease resistance, and are expected to be increasingly used in the search for tolerance to biotic and abiotic stresses. Their current and future use in crop improvement depends on their availability in ex situ germplasm collections. As these plants are impacted in the wild by habitat destruction and climate change, actions to ensure their conservation ex situ become ever more urgent. We analyzed the state of ex situ conservation of 73 of the closest wild relatives of potato (Solanum section Petota) with the aim of establishing priorities for further collecting to fill important gaps in germplasm collections. A total of 32 species (43.8%), were assigned high priority for further collecting due to severe gaps in their ex situ collections. Such gaps are most pronounced in the geographic center of diversity of the wild relatives in Peru. A total of 20 and 18 species were assessed as medium and low priority for further collecting, respectively, with only three species determined to be sufficiently represented currently. Priorities for further collecting include: (i) species completely lacking representation in germplasm collections; (ii) other high priority taxa, with geographic emphasis on the center of species diversity; (iii) medium priority species. Such collecting efforts combined with further emphasis on improving ex situ conservation technologies and methods, performing genotypic and phenotypic characterization of wild relative diversity, monitoring wild populations in situ, and making conserved wild relatives and their associated data accessible to the global research community, represent key steps in ensuring the long-term availability of the wild genetic resources of this important crop.